Different means to assess readiness to train among basketball athletes in a short-team period - Grincevicius, Stanislovas (2018)
Assessing athletes’ readiness to train might be particularly interesting area because higher workloads does not always enhance performance, but it might even decrease. In worst case scenario when increasing trainings’ frequency and workload, athletes can experience state of overreaching and eventually overtraining. That could stop athletes from exercising up to several months. Therefore, there are plenty of studies supporting variety of means to assess athletes’ recovery. However, as far as we know, none of the studies have investigated neuromuscular, salivary and sleep assessments in basketball players. The aim of the study was to investigate different means to detect fatigue and provide some insights for future projects. Subjects of the study were matured young athletes with international basketball experiences. Athletes were assessed in drop jumps, reaction time, salivary cortisol, sleep quality and quantity, rate of perceived exertion scale and two devices, sleep quality and neuromuscular fatigue, mostly prevailed in Finland. The results showed that single one variable could not determine athletes’ readiness to train. E.g., reactive strength index was not influenced by sleep, while reaction time and rate of perceived exertion were. Also, the study showed that athletes’ cortisol level at the beginning of the week and at the end of the week did not differ significantly. However, significant increase was observed after the official game. In summary, it is important to assess athletes state of being (physiological and psychological) but even more importantly to understand and plan the following sessions accordingly. While complex assessments might give thorough look and more comprehensive understanding in athlete’s performance, simple assessments are highly recommended for coaches to use.